Multi-objective optimization for a novel sandwich corrugated square tubes - Xiaolin Deng; Fumo Yang; Libo Cao; Jiale Huang (Alexandria Engineering Journal, 2023)
The sandwich corrugated square tubes (SCSTs), which includes outer square tube (OST), inner square tube (IST) and middle corrugated square tube (CST), have been has been proved to have excellent energy absorption performances. In order to further increase its performance and obtain the optimal structural parameters, multi-objective optimization of SCSTs is carried out. The surrogate modals for the SCSTs were constructed, and the main effects and the interaction effects were analyzed in detail. Finally, multi-objective particle swarm (MOPSO) optimization was used for multi-objective optimization of the SCSTs. The optimization results show that Pareto frontier of the SCSTs can reach a larger range than the SCSTs with A = 0 mm. Due to the coupling effect, energy absorption (EA) and initial peak force (Fmax) of the optimal design solution of the SCSTs are increased by 13.76% and decreased by 8.76% respectively compared to the sum of IST, OST and CST crushing alone. Two key indicators, including Fmax and EA, have been improved at the same time.